Comparison between two different efficiency improvement approaches for an obsolete small-size multi-generation plant. (August 2018) - Danti, Piero; Magnani, Sandro; Cauchi, Giovanni
Abstract: In the latest years, consumer's needs of reducing energy cost raised a general interest on plants upgrade and optimization; currently there are many approaches to deal with this tendency. Most intuitive way of proceeding is embodied by a revamping solution: often, above all in Italian landscape, small-medium size energy plants run outdated equipment whose performance have considerable room for improvement. Because of that, during last 15 years, many Energy Service Companies (ESCos) have been burgeoning providing a broad range of energy solutions. One of these solutions is represented by trigeneration systems installation, combining CHP and absorption chiller; by means of this a decrease of energy supply costs and CO2 emissions is achieved. Another philosophy to face the problem is the optimization of generators functioning using ad hoc control logics. This analysis aims to draw a comparison, from an economical point of view, between two different optimization strategies applied to the same small size energy plant where a cogeneration system is installed: the former strategy will focus on plant upgrade, substituting obsolete devices with higher performance ones, the latter will solely lean on an EMS running an optimization algorithm. Results will be presented and analysed in terms of daily costs.